Ibarbo Park brand activation strategy to increase consumer interest through the @ibarbopark TikTok account in 2024 (BIS Humanities and Social Science, 2026)
In the digital age, social media plays an important role in strengthening brand image and appeal. TikTok, as a short video-based platform with a high level of interaction, is used by Ibarbo Park to expand its marketing reach and build emotional connections with its audience. Therefore, the purpose of this study is to analyze Ibarbo Park's brand activation strategy in increasing consumer interest through its TikTok account @ibarbopark. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. Research informants include the head of the marketing division, the main figure behind TikTok content (Mr. Owner), and strategic content planners. Data analysis was carried out through the stages of reduction, data presentation, and conclusion drawing with validity testing using source triangulation. The results of the study show that Ibarbo Park's brand activation strategy was carried out using Regina Luttrell's Circular Model of SOME theory. The use of short comedy content and informative videos, active interaction through the comments section, and incentives such as vouchers and free tickets successfully increased engagement and created an emotional connection with the audience. In addition, the use of the “Pak Owner” character as a brand identity strengthened the brand's personality, making it memorable and likable to the public.